Structural Analysis and Design of Chionodracine-Derived Peptides Using Circular Dichroism and Molecular Dynamics Simulations - Stefano Borocci; Giulia Della Pelle; Francesca Ceccacci; Cristina Olivieri; Francesco Buonocore; Fernando Porcelli (International Journal of Molecular Sciences, 2020)
Antimicrobial peptides have been identified as one of the alternatives to the extensive use of common antibiotics as they show a broad spectrum of activity against human pathogens. Among these is Chionodracine (Cnd), a host-defense peptide isolated from the Antarctic icefish Chionodraco hamatus, which belongs to the family of Piscidins. Previously, we demonstrated that Cnd and its analogs display high antimicrobial activity against ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa and Enterobacter species). Herein, we investigate the interactions with lipid membranes of Cnd and two analogs, Cnd-m3 and Cnd-m3a, showing enhanced potency. Using a combination of Circular Dichroism, fluorescence spectroscopy, and all-atom Molecular Dynamics (MD) simulations, we determined the structural basis for the different activity among these peptides. We show that all peptides are predominantly unstructured in water and fold, preferentially as α-helices, in the presence of lipid vesicles of various compositions. Through a series of MD simulations of 400 ns time scale, we show the effect of mutations on the structure and lipid interactions of Cnd and its analogs. By explaining the structural basis for the activity of these analogs, our findings provide structural templates to design minimalistic peptides for therapeutics.